1992
DOI: 10.1002/dvg.1020130405
|View full text |Cite
|
Sign up to set email alerts
|

Broad‐Complex function during oogenesis in Drosophila melanogaster

Abstract: The Broad-Complex (BR-C) appears to encode factors that mediate ecdysone effects during the larva-adult transition. The main goal of this study was to gain insight into what roles the BR-C might play during oogenesis. The main findings are as follows. First, as determined by heteroallele studies and clonal analysis, de12 is a somatic line mutation that appears to fall into the broad domain of the BR-C. Second, the de12 mutation is associated with the insertion of the gypsy transposon at position 169.5 (Chao an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…X-Gal staining was observed in salivary glands, fat body, Malpighian tubules, gut, and brain during the third instar. Very specific traits, such as dotted expression in maxillary palps in late pupae, in agreement with the reduced bristles on palpus (rbp) phenotype (Kiss et al 1988), and expression in ovarian follicular cells, in agreement with the sterility and egg shell defects observed in some BRC mutants (Mazina et al 1991;Huang and Orr 1992), were observed (a detailed account will be published elsewhere). Considering what is presently known from molecular studies on the BRC temporal and tissular expression (Huet et al 1993;Karim et al 1993;Emery et al 1994}, the observed lacZ pattern in convertants can be interpreted as a partial image of the BRC expression.…”
Section: The Enhancer-trap Expression Patternsupporting
confidence: 56%
“…X-Gal staining was observed in salivary glands, fat body, Malpighian tubules, gut, and brain during the third instar. Very specific traits, such as dotted expression in maxillary palps in late pupae, in agreement with the reduced bristles on palpus (rbp) phenotype (Kiss et al 1988), and expression in ovarian follicular cells, in agreement with the sterility and egg shell defects observed in some BRC mutants (Mazina et al 1991;Huang and Orr 1992), were observed (a detailed account will be published elsewhere). Considering what is presently known from molecular studies on the BRC temporal and tissular expression (Huet et al 1993;Karim et al 1993;Emery et al 1994}, the observed lacZ pattern in convertants can be interpreted as a partial image of the BRC expression.…”
Section: The Enhancer-trap Expression Patternsupporting
confidence: 56%
“…The Z1 isoform of BR-C becomes expressed in the patches of follicular cells destined to form the dorsal appendages, and may be an upstream regulator of this process (Huang and Orr, 1992;Deng and Bownes, 1997).…”
Section: Chorion Genes and Regulation Of Chorion Gene Expression P0935mentioning
confidence: 99%
“…BRC mutants have common and complementation group-restricted phenotypes (Kiss et al 1988;White 1991, 1992;Huang and Orr 1992;Karim et al 1993;O'Keefe et al 1995;Sandstrom et al 1997;Liu and Restifo 1998;Mugat et al 2000;Brennan et al 2001;Consoulas et al 2005;Wilson et al 2006). Molecularly, BRC consists of a common 5′ exon, encoding a protein-binding region called BRcore, that is alternatively spliced to one of four tandemly duplicated 3′ exons, encoding zinc-finger-motif DNA-binding domains Z1, Z2, Z3, and Z4 (DiBello et al 1991;Bayer et al 1996).…”
mentioning
confidence: 98%